A greve em serviços essenciais e a atuação do Ministério Público do Trabalho - Momezzo, Marta Casadei (2007)
The aim of this paper is to demonstrate that strikes should only be called as ultima ratio, after negotiation attempts have completely failed. Striking has reached the status of a right and, as such, it is not an absolute right. When a strike breaks out involving the essential services, workers private interests conflict with the interests of society, which is extraneous to the conflict and deeply affected by it. In these cases, there is the obligation to assure the minimum services as a means of harmonizing the conflicting interests; otherwise, there is a risk the fundamental right to strike will be weakened. The determination of these minimum services by the Judiciary almost always conflicts with the strikers interests and it does not meet society s interests. Therefore, the best way is to establish procedures for the essential services strike by means of collective bargaining involving not only the participation of labor unions, but also the Ministério Público, representatives of the Government and the users of these services. Collective bargaining constitutes a prime instrument for the appeasement of labor conflicts and, for it to be effectively carried out, an environment of complete union freedom is required. The Constitutional Amendment no. 45/04 has brought great advancement in collective bargaining in our country for it conditioned the exercise of normative competence to common consent and authorized the action of collective bargaining in essential services striking by the Ministério Público do Trabalho in order to defend public interest solely. Besides that, with the existing instruments, it is already possible to enhance collective bargaining on condition that there is a change in the profile of citizens performance